RESISTENSI INSULIN TERKAIT OBESITAS: MEKANISME ENDOKRIN DAN INTRINSIK SEL - Mira Dewi (Jurnal Gizi dan Pangan, 2007)
The number of obese individuals worldwide has reached 2.1 billion and this will lead to explosion of obesity-related morbidity and mortality. Obese individuals will develop resistance to celluler action of insulin. The obesity related insulin resistance is the major risk factor of cardiovascular diseases and Type 2 Diabetes Mellitus, the disease which number has reached epidemic proportion. The association between obesity and insulin resistance seem to be cause and effect relation because studies on human and animal has indicated that the increase or decrease of body weight correlates with insulin sensitivity.  Among of many mechanisms proposed, the most often proposed mechanisms are endocrine and cell intrinsik mechanism. The increase of fatty acid plasma concentration, dysregulation of adipokines and ectopic fat storage are proposed to be the endocrin mechanism that lead to obesity related insulin resistance while oxidative stress and mitochondria dysfunction are the cell intrinsic mechanisms that play role to the disease. Understanding the molecular mechanisms of obesity related insulin resistance will provide valuable information to search for interventions that help to prevent or treat Type 2 Diabetes Mellitus and cardiovascular diseases and its related pathologies.